Understanding clinical and immunological features associated with Pseudomonas and Staphylococcus keratitis. Issue 1 (February 2021) - Shrestha, Gauri Shankar; Vijay, Ajay Kumar; Stapleton, Fiona; Henriquez, Fiona L.; Carnt, Nicole
Abstract: Pseudomonas aeruginosa and Staphylococcus aureus are the two dominant Gram-negative and -positive species, respectively, isolated from patients with contact lens-related bacterial keratitis. The clinical features of bacterial keratitis vary, such that timely differential diagnosis can be challenging, which may cause a delay in diagnosis resulting in poorer outcome. This review aims to explore the current understanding of clinical and immunological features associated with contact lens-related P. aeruginosa and S. aureus keratitis based on currently available evidence. Firstly, the review characterises contact lens-related P. aeruginosa and S. aureus keratitis, based on clinical features and prognostic factors. Secondly, the review describes the primary immune response associated with a bacterial infection in in-vivo non-scratch contact lens-wearing animal models, colonised by bacteria on contact lens and topical administration of bacteria on the cornea. Finally, the review discusses the role of macrophage inflammatory protein-2 (MIP-2) and intercellular adhesion molecule (ICAM-1) in neutrophil recruitment based on both in-vivo scratch models of bacterial keratitis and bacterial challenged in cell culture models.